THE PLANNING OF ARTIFICIAL RECHARGED WELLS AT PURI BUNGA NIRWANA, BUKIT PERMAI, AND GUNUNG BATU HOUSINGS AT JEMBER: Perencanaan Sumur Resapan di Kawasan Perumahan Puri Bunga Nirwana, Perumahan Bukit Permai, dan Perumahan Gunung Batu - Wahyuni, Sri; Halik, Gusfan; Wulandari, Wahyu Sri (Universitas Jember, 2018)
Puri Bunga Nirwana, Bukit Permai, and Gunung Batu Housings are some of the housings that exist in Sumbersari subdistrict. These housings are the third former residential land that was initially able to rainwater seeped into the land of the free but is now covered by housing buildings. The effect of this case is the water cannot go into the land directly but the weather even in times of flooding rains. Therefore, to overcome this problem, it is necessary to do a study and planning of artificially recharged wells in the area. From the result of research with the basic circle and square pad at Puri Bunga Nirwana Housings for the types of houses with an area of 72 m2, 84 m2, and 105 m2 were made artificial recharged wells with a diameter of 1 m and a depth of 2 m. While at Bukit Permai and Gunung Batu Housings for the types of houses with an area of 75 m2, 90 m2, 101 m2, and 202 m2 were made artificial recharged wells with a diameter of 1 m and a depth of 2 m. And the useful cross-section used on each housing is the square cross-section. Perumahan Puri Bunga Nirwana, Perumahan Bukit Permai dan Perumahan Gunung Batu merupakan beberapa perumahan yang ada di Kecamatan Sumbersari. Ketiga perumahan ini dahulunya merupakan lahan yang awalnya mampu meresap air hujan ke dalam tanah secara bebas akan tetapi kini tertutup oleh bangunan-bangunan perumahan. Hal ini menyebabkan air tidak dapat langsung masuk ke dalam tanah tetapi menggenang bahkan banjir di saat hujan turun. Oleh karena itu, untuk mengatasi permasalahan ini perlu dilakukan perencanaan sumur resapan di daerah tersebut. Dari hasil penelitian dengan penampang lingkaran dan penampang persegi pada Perumahan Puri Bunga Nirwana untuk tipe rumah dengan luas 72 m2, 84 m2, dan 105 m2 dibuat sumur resapan dengan diameter 1,0 m dan kedalaman 2,0 m. Pada Perumahan Bukit Permai dan Perumahan Gunung Batu untuk tipe rumah dengan luas 75 m2, 90 m2, 101 m2 dan 202 m2 dibuat sumur resapan dengan diameter 1,0 m dan kedalaman 2,0 m.dari hasil perhitungan diketahui bahwa penampang yang efektif digunakan pada masing-masing perumahan adalah penampang persegi.